DINAMIKA PEMBANGUNAN MANUSIA DAN PENGANGGURAN DALAM KONTEKS KEPENDUDUKAN DI DESA BLIMBING PAKUNIRAN - Mea Wulandari; Rini Andriani (PT. Saha Kreasi Indonesia, 2026)
Taking into account demographic factors as a driving force, this study investigates the dynamics of human development and unemployment rates in Blimbing Village, Pakuniran District. It is shown that there is a significant correlation between human development measured through education, health, and economic indicators. This study found that several main challenges for Blimbing Village development are low quality of human resources, limited access to high-quality education, and few formal employment opportunities. These challenges were identified through descriptive quantitative research methods using a survey approach. This research demonstrates that, in addition to enhancing local economic diversification, investment in education and skills training, and strengthening the agricultural sector and MSMEs can be effective strategies to improve the Human Development Index (HDI) while simultaneously reducing unemployment rates. This study provides policy recommendations to assist village government and related stakeholders in creating inclusive and sustainable development programs.